Nitric oxide activatable photosensitizer accompanying extremely elevated two-photon absorption for efficient fluorescence imaging and photodynamic therapy - Hu, Wenbo (Royal Society of Chemistry, 2017)

(untitled) (Chem Sci)
Elevated nitric oxide (NO) levels perform an important pathological role in various inflammatory diseases. Developing NO-activatable theranostic materials with a two-photon excitation (TPE) feature is highly promising for precision imaging and therapy, but constructing such materials is still a tremendous challenge. Here, we present the first example of a NO-activatable fluorescent photosensitizer (DBB-NO) accompanying extremely NO-elevated two-photon absorption (TPA) for efficient fluorescence imaging and photodynamic therapy (PDT). Upon responding to NO, DBB-NO shows not only a remarkably enhanced fluorescence quantum yield (Φ(F), 0.17% vs. 9.3%) and singlet oxygen quantum yield (Φ(Δ), 1.2% vs. 82%) but also an extremely elevated TPA cross-section (δ, 270 vs. 2800 GM). Simultaneous enhancement of Φ(Δ), Φ(F) and δ allows unprecedented two-photon fluorescence brightness (δ × Φ(F) = 260.4 GM) and two-photon PDT (TP-PDT) efficiency (δ × Φ(Δ) = 2296 GM) which precedes the value for a commercial two-photon photosensitizer by two orders of magnitude. With these merits, the proof-of-concept applications of NO-activatable two-photon fluorescence imaging and TP-PDT in activated macrophages (in which NO is overproduced) were readily realized. This work may open up many opportunities for constructing two-photon theranostic materials with other pathological condition-activatable features for precise theranostics.